Systematic Review of Impact-Driven Analytics Metrics for Strategic Enterprise Decision-Making - Adaobi Beverly Akonobi,; Christiana Onyinyechi Makata, (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
In an increasingly data-driven business environment, organizations face growing pressure to ensure that analytics outputs meaningfully influence strategic decision-making. Traditional metrics often emphasize operational performance without directly linking to business impact, creating a gap between data insights and executive action. This systematic review investigates the evolution, application, and effectiveness of impact-driven analytics metrics within strategic enterprise decision-making frameworks. Drawing from academic research, industry whitepapers, and case studies, the review synthesizes best practices for designing, implementing, and operationalizing metrics that prioritize tangible business outcomes. Key focus areas include outcome-based key performance indicators (KPIs), leading versus lagging metrics, customer-centric impact measurements, and financial value attribution. The study explores methodologies such as OKRs (Objectives and Key Results), North Star metrics, and balanced scorecard approaches to align analytics efforts with organizational goals. Special attention is given to the role of real-time metrics, predictive analytics, and AI-driven insight generation in enabling proactive strategy adjustments. Challenges such as metric overload, misalignment between analytics teams and business units, and difficulties in quantifying qualitative outcomes are critically analyzed. Additionally, the paper reviews technological enablers including metric layer solutions, dashboarding tools, and advanced data platforms that facilitate impact-driven measurement. Case examples from industries such as healthcare, technology, and financial services illustrate how enterprises translate impact-driven analytics into competitive advantage, innovation, and operational excellence. Future directions emphasize dynamic metric frameworks that adapt to market changes, integration of causal inference models, and the evolution of autonomous analytics systems that continuously refine impact measurements. By systematically reviewing current practices and emerging innovations, this paper offers a comprehensive foundation for enterprises seeking to redesign their analytics functions around business impact rather than mere activity tracking, ultimately empowering better, faster, and more strategic decisions.
Keywords: Impact-driven analytics; strategic decision-making; outcome-based KPIs; enterprise metrics; OKRs; North Star metrics; predictive analytics; business value measurement; balanced scorecard; autonomous analytics systems